Pengembangan Perusahaan Berbasis Nilai Islam pada Digital Startup - Safitri Maya Nastiti (Indonesian Center for Religion and Society Studies (InTReSt), 2019)
Lots of studies argue that company development is determined by innovation, adaptability, and institutional dynamism. This study aims to explain the development of islamic value-based companies in digital startups, whereas the success factor of company is not only determined by innovation, adaptability, and institutional dynamism, but precisely caused by role of islamic values which was developed by the companies. Through qualitative approach, this results of study show that the islamic values which are the foundation of the company in carrying out to all operations of institution are Tauhid, Qonaah, competent, and moral. These islamic values at PT. Badr Interactive is built through the regulatory, normative, and cognitive cultural pillars. In general, islamic values play a role in four human resources, marketing, social responsibility, and corporate culture aspects. The influence of islamic values in these aspects produces an output of good quality product applications, good teamwork, strong employee resilience, employee spiritual needs, planned marketing strategies. These indicators are digital startup companies sources of success.